MICROLEARNING AND NANOLEARNING IN HIGHER EDUCATION: A BIBLIOMETRIC REVIEW TO IDENTIFY THEMATIC PREVALENCE IN THE COVID-19 PANDEMIC AND POST-PANDEMIC CONTEXT - CHAMORRO-ATALAYA, OMAR (2024)
THE COVID-19 PANDEMIC LED TO A SIGNIFICANT SHIFT TOWARDS MORE INNOVATIVE TEACHING METHODS, HIGHLIGHTING THE NEED FOR CONTINUOUS AND FLEXIBLE LEARNING APPROACHES. THUS, IT IS RELEVANT TO EXPLORE THE CASUISTRY OF THE VARIOUS APPLICATIONS OF MICROLEARNING AND NANOLEARNING IN HIGHER EDUCATION, AND IDENTIFY THE THEMATIC TRENDS AND TOPICS LITTLE EXPLORED IN THE PANDEMIC AND POST-PANDEMIC SCENARIO. IN THIS SENSE, THE PURPOSE OF THIS STUDY IS TO CARRY OUT A BIBLIOMETRIC REVIEW UNDER A QUANTITATIVE APPROACH AND AT AN EXPLORATORY-DESCRIPTIVE LEVEL, ON THE EXISTING LITERATURE IN THE SCOPUS DATABASE. AS A RESULT, IT WAS POSSIBLE TO IDENTIFY THAT THE COVID-19 PANDEMIC HAS INFLUENCED SCIENTIFIC PRODUCTION IN THE APPLICATION OF MICROLEARNING IN HIGHER EDUCATION TO A GREATER EXTENT WITH RESPECT TO NANOLEARNING. FURTHERMORE, THE PREVALENT THEMES IDENTIFIED IN THE EXISTING LITERATURE ARE THE EFFECTIVENESS AND ADAPTATION OF MICROLEARNING IN DIFFERENT AREAS OF HIGHER EDUCATION, SUCH AS MEDICINE AND ENGINEERING, THE DEVELOPMENT OF COMPETENCIES AND SKILLS THROUGH MICROLEARNING IN UNIVERSITY STUDENTS AND THE EVALUATION OF THE IMPACT OF INNOVATIVE TEACHING STRATEGIES SUCH AS MICROLEARNING IN HIGHER EDUCATION. THEREFORE, IT IS CONCLUDED THAT, IN THE CURRENT POST-PANDEMIC CONTEXT, A CLEAR FOCUS ON THE APPLICATION, INTEGRATION AND EVALUATION OF THE IMPACT OF MICROLEARNING IN HIGHER EDUCATION PREVAILS; HOWEVER, A SIGNIFICANT GAP IS IDENTIFIED IN THE ADOPTION OF NANOLEARNING, WHICH IS IN AN EMERGING PHASE OF DEVELOPMENT. ©AUTHORS.